Chemical Composition of the Essential Oil and Diethyl Ether Extract of Trinia glauca (L.) Dumort. (Apiaceae) and the Chemotaxonomic Significance of 5‐O‐Methylvisamminol. Issue 4 (April 2016) - Radulović, Niko S.; Đorđević, Miljana R.; Dekić, Milan S.; Blagojević, Polina D.
Abstract : Analyses by GC, GC/MS, and NMR spectroscopy (1D‐ and 2D‐experiments) of the essential oil and Et2 O extract of Trinia glauca (L .)Dumort . (Apiaceae) aerial parts allowed a successful identification of 220 constituents, in total. The major identified compounds of the essential oil were ( Z )‐falcarinol (10.6%), bicyclogermacrene (8.0%), germacrene D (7.4%), δ ‐cadinene (4.3%), and β ‐caryophyllene (3.2%), whereas ( Z )‐falcarinol (47.2%), nonacosane (7.4%), and 5‐ O ‐methylvisamminol (4.0%) were the dominant constituents of the extract of T. glauca . One significant difference between the compositions of the herein and the previously analyzed T. glauca essential oils (only two reports) was noted. ( Z )‐Falcarinol was the major constituent in our case, whereas germacrene D (14.4 and 19.6%) was the major component of the previously studied oils. Possible explanations for this discrepancy were discussed. 5‐ O ‐Methylvisamminol, a (furo)chromone identified in the extract of T. glauca, has a limited occurrence in the plant kingdom and is a possible excellent chemotaxonomic marker (family and/or subfamily level) for Apiaceae. Abstract :